The relationship between blood antioxidant enzyme levels and genotype during migraine attack and initial periods in migraine patients - Özbey, Ülkü; Özel, Seda; Seyran, Ayşe; Erişir, Mine; Berilgen, M. Said (Turkish Biochemistry Society, 2011)
Objective: In recent years, researchers have been focused on the importance of oxidative stress on migraine pathogenesis. We aimed to investigate the roles of Superoxide Dismutase (SOD), Glutathione Peroxidase (GSH-Px), Catalase (CAT), antioxidant Glutathione (GSH) and Malondialdehyde (MDA) of a lipid peroxidation product in migraine pathogenesis. Furthermore, we also aimed to investigate the incidence of the gene polymorphisms of these enzymes in Turkish population. Material and Methods: GSH-Px, CAT, SOD activities and plasma MDA and blood GSH levels were measured in 40 migraine patients at attack and initial period and 40 healthy subjects. The genotype characteristics were determined by PCR-based RFLP method using DNA extracted from peripheral blood. Results: Statistically significant decrease in GSH-Px, CAT, SOD activities and GSH levels were found in the migraine patients compared to the control group (GSH, CAT p<0.001; GSH-Px, SOD p<0.05). In the migraine patients and control groups no significant differences were observed for Mn-SOD and CAT genotypes, but there was a significant difference in the GSH-Px3 genotype. No difference was detected in the allele frequencies of MnSOD, GSH-Px3 and CAT gene between the patients and control group. Conclusion: Consequently, oxidative stress and antioxidant enzymes may play an important role in migraine pathogenesis, and according to our data GSH-Px3 gene polymorphism may cause a tendency to migraine for our regional community. Conflict of Interest: There is no conflict of interest between autors. © TurkJBiochem.com.
Atak ve atak dışı dönemdeki migren hastalarında kan antioksidan enzim düzeyleri ve genotip arasındaki i?lişki
Keywords: Catalase; Glutathione peroxidase-3; Manganese superoxide dismutase; Migraine; Polymorphism